Upaya Meningkatkan Partisipasi Dan Hasil Belajar Siswa Dengan Menggunakan Metode Diskusi Kelompok Pada Mata Pelajaran IPS Terpadu Kelas VIII Di SMP Negeri 19 Padang - Ebit Bimas Saputra; Evan Saputra; Nofri Satriawan (PAKAR Pendidikan, 2019)
This research is motivated by the problem of the learning methods of group discussion in the purpose of this study is to find out how to increase participation and learning outcomes in learning Integrated Social Sciences discussion methods in class VIII.3 in SMP 19 Padang. The results of data analysis show that learning group discussion models can increase student activity. Students have the courage to ask questions, communicate, answer questions from teachers, friends or other groups and dare to defend their opinions when discussing. Increased participation and Integrated Social Studies learning outcomes can be seen from the acquisition of student scores before being given action, which is an average of 74, to 78 in cycle I. Achievement of material completeness before the action was 8 students (26.67%), increasing to 12 students ( 40%) in cycle I. In the second cycle the average value increased to 83.77 and students who had achieved completeness 23 students (76.67%) at the end of the cycle test the average score of students became 87.1 students who had achieved completeness 26 students (86.67 %). From the results of the study, it can be concluded that the learning method of Group Discussion is able to increase student participation in class VIII. 3 at SMP N 19 Padang, because learning using the Group Discussion method can create an active, innovative, creative and enjoyable learning atmosphere.